Vijay Padaki and Manjulika Vaz. Institutional Development in Social Interventions: Towards Inter-organizational Effectiveness. New Delhi: Sage Publications, 2003. 256 pages. Indian Rs 295.00. (The Pakistan Development Review, 2005)
Is an institution the same as an organisation? Why do organisations organise themselves into institutional forms? What makes some institutions more successful than others? How do we define and assess ‘success’? Does institutionalisation require formalisation? How do we go about building and developing institutions? These are some of the questions that are the subject matter of the book under review. It was a research project undertaken by a Bangalore-based management research and consultancy centre from 1997 to 1999 that provided the necessary impetus and focus for institutional development in the special context of development interventions. This book is in the nature of a presentation of a work-in-progress and not merely a report of a research project.